2015
DOI: 10.1039/c4ay02579b
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and separation of triazine herbicides in soybean by ionic liquid foam-based solvent flotation and high performance liquid chromatography determination

Abstract: Ionic liquid foam-based solvent flotation coupled with high performance liquid chromatography was developed for the extraction, separation and determination of four triazine herbicides from soybean samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Relatively stable liquid foams can be used in fire-fighting, 26 oil-drilling, 27 and flotation, 28 etc. For papermaking, fibers are usually fibrillated (refined) and mixed with additives in aqueous dispersions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Relatively stable liquid foams can be used in fire-fighting, 26 oil-drilling, 27 and flotation, 28 etc. For papermaking, fibers are usually fibrillated (refined) and mixed with additives in aqueous dispersions.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 3 The extraction efficiency started to drop at pH 6 and above because of atrazine (deprotonated) hydrolysed in alkali environment. 29 Based on Fig. 1 , both the CPE methods using OFX 0309 and DC 193C showed a similar trend in the effect of pH.…”
Section: Resultsmentioning
confidence: 74%
“…In addition to heavy metal ions, ion otation is also commonly used for removing organic and biological pollutants such as oil, triazine herbicides, peruorooctane sulfonate (PFOS) and peruorooctanoate, Rhodamine 6G and sulfonylurea herbicides from wastewater or aqueous solution. [41][42][43][44][45][46][47] Lignin removal research was conducted by Wang et al through ion otation using cetyl dimethyl benzyl ammonium as the surfactant. They found that a fraction of more than 0.95 could be removed by continuous ion otation under the optimum operational conditions.…”
Section: Wastewater Treatmentmentioning
confidence: 99%